Influence of Escherichia coli lipopolysaccharide induced fever on the plasma kinetics of pazufloxacin in buffalo calves - SHARMA, S K; ADITI, ADITI; UL HAQ, SHAH AHSAN (The Indian Journal of Animal Sciences, 2014)
The pharmacokinetics of pazufloxacin was studied in healthy and febrile buffalo calves (5 mg/kg, IV). The fever was induced with Escherichia coli lipopolysaccharide. The drug concentration in plasma was detected by HPLC method. At 2.5 min the concentration of pazufloxacin in healthy and febrile animals were 17.8 0.6 µg/ml and 15.4±0.5 mg/ml, respectively and drug was detected up to 16 h. The distribution half-life of pazufloxacin increased from 0.09±0.01 h in healthy animals to 0.16±0.01 h in febrile animals. Drug distribution was altered by fever as febrile animals showed higher volume of distribution (1.35 0.09 L/ kg) higher than normal animal (1.03±0.06 L/kg). Total body clearances in healthy and febrile animals were 539.7±28.3 and 510.6±18.2 ml/kg/h, respectively. To maintain minimum therapeutic concentration of 0.1 µg/ml, a satisfactory dosage regimen of pazufloxacin in healthy and febrile buffalo calves would be 4.7 mg/kg and 4 mg/kg body weight, respectively, to be repeated at 12 h intervals.